Impact of Bank Size on Performance of Nepalese Commercial Banks - Adhikari, Khagendra; Poudel, Chet Nath; Shrestha, Bikash; Timsina, Sunil (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2023)
Banks play an important role in an economy. Bank size is one of the important factors of banks to perform and generate revenue and profits. This study aimed to analyze the types of relation between bank size and bank performance. This study was based on 10 years’ hand collected secondary quantitative data from 20 commercial banks leading 200 observations. Descriptive, correlational, and causal-comparative research designs were employed. Descriptive statistics was applied to compute summarized values of study variables. Correlation analysis was applied to measure the association between dependent and independent variables. Factor analysis was employed to develop surrogate size variable. Finally, linear and nonlinear regression models were applied to measure causal relation between bank size variables and performance variables. The results showed that there was not a linear relationship between bank size variables and bank performance variables, but it found nonlinear relationship between them. It indicated that there was a threshold value of bank size variables that maximized the bank performance.